(untitled) (Bioscience Journal, 2019)
At maximum vegetative growth, sprays with fungicide to control Asian rust (Phakopsora pachyrhizi Sydow and P. Sydow) should reach high canopy penetration and plant coverage. Therefore, the central objective of this study was to determine leaf area, spray deposition, and plant coverage by fungicides sprayed on soybeans as a function of sowing seasons and plant population densities with reduced doses of tebuconazole and azoxystrobin + cyproconazole. Field experiments were conducted in the 2009/2010 and 2010/2011 crop years, using a medium-cycle soybean cultivar MG/BR–46 (Conquista) under a natural infestation of Asian soybean rust. Leaf area (LA) and leaf area index (LAI) were measured at three developmental stages (V8, R2, and R4). Spray deposition and coverage were evaluated during the first fungicide spraying. As results, LAI decreased as plant population decreased. Despite the lower LAIs, smaller plant populations had no effect on spray deposition and plant coverage. Both fungicides presented similar depositions on all thirds when plants had lower development.